Twenty-five year experience with aortic valve-sparing root replacement in a single teaching center - Sromicki, Juri; Van Hemelrijck, Mathias; Schmiady, Martin O.; Greutmann, Matthias; Bonassin Tempesta, Francesca; Mestres, Carlos-A.; Vogt, Paul R.; Carrel, Thierry P.; Holubec, Tomáš (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Objectives Aortic valve-sparing root replacement (AVSRR) is a technically demanding procedure. In experienced centers it offers excellent short- and long-term results, making the procedure an attractive alternative for aortic root replacement especially in young patients. The aim of this study was to analyze long-term results of AVSRR using the David operation in our institution over the last 25 years. Methods This is a single-center retrospective analysis of outcomes of David operations performed in a teaching institution not running a large AVSRR-program. Pre-, intra- and postoperative data were collected from the institutional electronic medical record system. Follow-up data were collected through direct contact of the patients and their cardiologists/primary care physicians. Results Between 02/1996 and 11/2019, 131 patients underwent David operation in our institution by a total of 17 different surgeons. Median age was 48 [33-59], 18% were female. Elective surgery was performed in 89% of the cases, 11% were operated as emergency in the setting of an acute aortic dissection. Connective tissue disease was present in 24% and 26% had a bicuspid aortic valve. At hospital admission 61% had aortic regurgitation grade ≥3, 12% were in functional NYHA-class ≥III. 30-day mortality was 2%, 97% of the patients were discharged with aortic regurgitation ≤2. In 10-year follow-up, 15 (12%) patients had to be re-operated because of root-related complications. Seven patients (47%) received a transcatheter aortic valve implantation, 8 (53%) required surgical replacement of the aortic valve or a Bentall-De Bono operation. Estimated reoperation-free survival at 5 and 10 years was 93.5% ± 2.4% and 87.0% ± 3.5%, respectively. Subgroup analysis showed no differences in reoperation-free survival for patients presenting with a bicuspid valve or preoperative aortic regurgitation ≥3. However a preoperative left ventricular end diastolic diameter of ≥5.5cm was associated with worse outcome. Conclusions David operations can be performed with excellent perioperative and 10-year follow-up outcomes in centers not running large AVSRR-programs.